AN IT2FS MODEL FOR SHARIA CREDIT SCORING: ANALYSIS & DESIGN - Galih Kurniawan Sidik; Taufik Djatna; Agus Buono (Jurnal Sistem Informasi, 2013)
Credit scoring system is a classic problem which is still interesting to study. There are many studies on credit scoring. But, most of them only discuss feasibility analysis. In fact, credit scoring system should accommodate all processes from feasibility analysis until the end of contract. This study is aimed to analyze and design scoring of default status and ﬁnes computation processes in Islamic bank. BPMN 2.0 was used to model their processes. Beside that, this study proposed new mechanisms and algorithms using Interval Type-2 Fuzzy Sets for maintaining Sharia rules and fairness guarantee. The results showed that the new methods offer more fair and comply to sharia than existing methods.